Metagenomic analysis reveals genetic insights on biogeochemical cycling, xenobiotic degradation, and stress resistance in mudflat microbiome - Mohapatra, Madhusmita; Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh S.; Rastogi, Gurdeep (Journal of Environmental Management, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Mudflats are highly productive coastal ecosystems that are dominated by halophytic vegetation. In this study, the mudflat sediment microbiome was investigated from Nalabana Island, located in a brackish water coastal wetland of India; Chilika, based on the MinION shotgun metagenomic analysis. Bacterial, archaeal, and fungal communities were mostly composed of Proteobacteria (38.3%), Actinobacteria (20.7%), Euryarchaeota (76.1%), Candidatus Bathyarchaeota (6.8%), Ascomycota (47.2%), and Basidiomycota (22.0%). Bacterial and archaeal community composition differed significantly between vegetated mudflat and un-vegetated bulk sediments. Carbon, nitrogen, sulfur metabolisms, oxidative phosphorylation, and xenobiotic biodegradation were the most common microbial functionalities in the mudflat metagenomes. Furthermore, genes involved in oxidative stresses, osmotolerance, secondary metabolite synthesis, and extracellular polymeric substance synthesis revealed adaptive mechanisms of the microbiome in mudflat habitat. Mudflat metagenome also revealed genes involved in the plant growth and development, suggesting that microbial communities could aid halophytic vegetation by providing tolerance to the abiotic stresses in a harsh mudflat environment. Canonical correspondence analysis and co-occurrence network revealed that both biotic (vegetation and microbial interactions) and abiotic factors played important role in shaping the mudflat microbiome composition. Among abiotic factors, pH accounted for the highest variance (20.10%) followed by available phosphorus (19.73%), total organic carbon (9.94%), salinity (8.28%), sediment texture (sand) (6.37%) and available nitrogen (5.53%) in the mudflat microbial communities. Overall, this first metagenomic study provided a comprehensive insight on the community structure, potential ecological interactions, and genetic potential of the mudflat microbiome in context to the cycling of organic matter, xenobiotic biodegradation, stress resistance, and in providing the ecological fitness to halophytes. These ecosystem services of the mudflat microbiome must be considered in the conservation and management plan of coastal wetlands. This study also advanced our understanding of fungal diversity which is understudied from the coastal lagoon ecosystems.